RNA m6A modification orchestrates the rhythm of immune cell development from hematopoietic stem cells to T and B cells - Zhao, Chuanxiang; Xu, Guoying; Zhang, Xiaoxian; Ye, Yunfeng; Cai, Weili; Shao, Qixiang (Frontiers in Immunology, 2022)
RNA, one of the major building blocks of the cell, participates in many essential life processes. RNA stability is well-established to be closely related to various RNA modifications. To date, hundreds of different RNA modifications have been identified. N6-methyladenosine (m6A) is one of the most important RNA modifications in mammalian cells. An increasing body of evidence from recently published studies suggests that m6A modification is a novel immune system regulator of the generation and differentiation of hematopoietic stem cells (HSCs) and immune cells. In this review, we introduce the process and relevant regulatory mechanisms of m6A modification and summarize recent findings of m6A in controlling HSCs generation and self-renewal, the development and differentiation of T and B lymphocytes from HSCs and discuss the potential mechanisms involved.